The Legal Understanding of Restaurant Entrepreneurs On Halal Certification After The Enactment Omnibus Law and Government Regulation No. 39 of 2021 - Yuniar Ika Sukmawati (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Halal certification is an obligation as protection and certainty consumer law that is regulated in Job Creation Law and PP No.39 of 2021 concerning Implementation of Halal Product Assurance. One of the provisions is about Self Declare. However, still many restaurants in Lowokwaru district, Malang City haven’t been certified halal. This study aimed to know the legal understanding of restaurant entrepreneurs on halal certification and to determine the legal consequences of entrepreneurs who haven’t halal certification perspective Job Creation Law and BPJPH. This research method used a juridical-empirical with a sociological-jurisprudence approach. Data collection with questionnaire and interview. The results showed that the legal understanding of restaurant entrepreneurs on halal certification was less understood. They haven’t understood the provisions of Self Declare and the period of termination of halal certification. So far no one article regulated the legal consequence, but entrepreneurs who haven’t been certified halal will get social consequences excluded from entrepreneurs who have been certified halal. Administrative sanctions of written reprimand in advance become a possible alternative conducted by Halal Product Assurance Agency (BPJPH).